Developing Competences Designed to Create Customer Value - Anna Lund Jepsen; Svend Ole Madsen (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2006)
This paper focuses on how small, specialized suppliers can gain competitive advantage by acting as a potential for their scale intensive producing customers in achieving competitive advantage. Of special interest is how a shared under-standing of value for the customer is obtained, transferred and implemented in the specialized suppliers production of process equipment. The study draws on theory on networks and specialized suppliers as well as interviews with key in-formants in three specialized supplier companies for the aluminum industry. An important finding is that the constellation of the specialized suppliers network changes as the project moves from planning to production. With these changes, the role of specialized suppliers in the value creation process also changes. It seems to be an important competence for small, specialized supplier to be able to draw on and manage this network in their value creation process.
Keywords: 330